Analisis Sentimen Film Kuliah Kerja Nyata (Kkn) Di Desa Penari Menggunakan Metode Naive Bayes - Salsa Bella Putri; Yonawati Nur Anisa; Nurirwan Saputra (Universitas Katolik Musi Charitas, 2022)
The film of Kuliah Kerja Nyata (KKN) in the Dancing Village which is being discussed among the Indonesian people is a film based on a novel by a simpleman entitled